YANG DALAM BAHASA INDONESIA - I Nengah Mileh; Ida Bagus Astika Pidada (Universitas Warmadewa, 2023)
This research entitled â€œYang in Indonesian languageâ€. The word yang is as one of the language Aspects that must be studied to get the clear usage. Particle yang has some identities and functions. This research aims to find out the identities and functions of yang in Indonesian language. In collecting the data, observation and note-taking techniques were employed. In analyzing the data, distribusional method and substitution technique were applied. In presenting the result of the analysis, informal method was used. This study finds out three identities of yang namely 1) yang as particle, 2) yang as conjunction, and 3) yang as noun builder. In addition, yang has two functions in Indonesian language, namely yang functions as clause conjunction and yang functions as noun substitution. Keywords: yang, particle, conjunction